A conjecture about the neural basis of recursion in light of descent with modification. (August 2017) - Boeckx, Cedric
Abstract: The goal of this paper is to examine the possible neurobiological basis of a defining property of the human language faculty: recursion. I suggest that recursion should be understood in light of Darwinian's descent with modification. Descent: that is, based on ingredients of neural circuitry found in 'non-linguistic' species; and modification: a reconfiguration that is specific to anatomically modern humans. I argue that the expansion of the parietal region associated with the globularization of the neurocranium in our species contributed to the transformation of the connection between Broca's and Wernicke's region via Geschwind's territory, and enabled the pairing of evolutionary ancient networks that together became capable of constructing and processing not just sequences, but sequences of sequences. Highlights: Examine the neural basis of recursion. Offer a plausible descent-with-modification scenario Link recursion and distinct ontogenetic trajectory of human brain (globularity).